Answer:
Simplifying
75 = 2x + -1
Reorder the terms:
75 = -1 + 2x
Solving
75 = -1 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
75 + -2x = -1 + 2x + -2x
Combine like terms: 2x + -2x = 0
75 + -2x = -1 + 0
75 + -2x = -1
Add '-75' to each side of the equation.
75 + -75 + -2x = -1 + -75
Combine like terms: 75 + -75 = 0
0 + -2x = -1 + -75
-2x = -1 + -75
Combine like terms: -1 + -75 = -76
-2x = -76
Divide each side by '-2'.
x = 38
Simplifying
x = 38
Step-by-step explanation: